Validation of diabetes medication self-efficacy scale in Chinese with type 2 diabetes - Zheng J (Patient Preference and Adherence, 2018)
Jiezhong Zheng,1 Yeli Wang,2 Xiangrong Ye,3 Ling Xiao,4 Junting Ye,5 Xiaoru Li,6 Mingkang Zhong1 1Department of Pharmacy, Huashan Hospital, Fudan University, Shanghai 200040, China; 2Health Services and Systems Research, Duke-NUS Medical School, Singapore 169857, Singapore; 3Department of Endocrinology, Xiamen Municipal Hospital of Traditional Chinese Medicine, Xiamen 361009, China; 4Department of Endocrinology, Jinshan Hospital of Fudan University, Shanghai 201508, China; 5School of Basic Medical Sciences, Fujian Medical University, Fuzhou 350001, China; 6Department of Psychology, School of Social Development and Public Policy, Fudan University, Shanghai 200433, China Aims: Greater diabetes medication self-efficacy has been shown to associate with better medication adherence, which is critical for disease control for people living with type 2 diabetes (T2D). The Diabetes Medication Self-efficacy Scale (DMSS) is a 19-item instrument to measure diabetes medication self-efficacy. The aim of the current study was to translate the DMSS into Chinese and validate the Chinese version of DMSS (CDMSS) among Chinese T2D patients. Methods: The CDMSS was translated using forward–backward method, and its validity and reliability were assessed among 257 Chinese T2D patients. Exploratory factor analysis, Cronbach’s α and Spearman’s rank correlation coefficients were used to evaluate the psychometric properties of CDMSS. Receiver operating characteristic analysis was used to assess the discrimination of CDMSS for medication adherence and glycemic control. Results: Exploratory factor analysis has generated a one-factor structure of the 11-item version of CDMSS (CDMSS-11), which accounted for 63.1% of the variance. The Spearman’s rank correlation coefficient between the original 19-item and 11-item scale was 0.96. The Cronbach’s α for internal consistency was 0.94, and the test–retest reliability coefficient was 0.76. The CDMSS-11 score was significantly correlated with diabetes distress, medication adherence, as well as blood levels of fasting plasma glucose and hemoglobin A1c (both P<0.001). The area under receiver operating characteristic curve and its corresponding 95% CI was 0.79 (0.73–0.84) for medication adherence, and it was 0.65 (0.57–0.72) for better glycemic control. Conclusion: The CDMSS-11 is a valid and reliable measure to assess medication self-efficacy among Chinese T2D patients. Keywords: medication adherence, medication self-efficacy, type 2 diabetes, validation study